Intraperitoneal chemotherapy in the management of ovarian cancer: focus on carboplatin - Maurie Markman (Therapeutics and Clinical Risk Management, 2009)
Maurie MarkmanUniversity of Texas MD Anderson Cancer Center, Houston, Texas, USAAbstract: Both pre-clinical studies and phase 1–2 clinical trials have provided strong support for the potential role of regional drug delivery in the management of epithelial ovarian cancer, a disease process whose major manifestations remain largely localized to the peritoneal cavity in the majority of individuals with this malignancy. The results of 3 phase 3 randomized trials have revealed the favorable impact of primary cisplatin-based intraperitoneal chemotherapy in women who initiate drug treatment with small-volume residual ovarian cancer following an attempt at optimal surgical cytoreduction. Concerns have been raised regarding the toxicity of regional treatment, particularly the side-effect profile associated with cisplatin. One rational approach to improving the tolerability of intraperitoneal chemotherapy is to substitute carboplatin for cisplatin. This review discusses the rationale for and data supporting regional treatment of epithelial ovarian cancer, and highlights the potential role for intraperitoneal carboplatin in this clinical setting.Keywords: ovarian cancer, intraperitoneal chemotherapy, cisplatin, carboplatin